Scaling Gender-Smart Agriculture through Sustainable Finance in the Sahel - Costa, Ciniro; Derenoncourt, Marie Ena; Masika, Daniel; Mufti, Samaa; Newman, Richard; Grosjean, Godefroy (CGIAR System Organization, 2022)
A rapid Climate-Smart Agriculture (CSA) assessment was conducted on 20 agri-food companies supported by the Gender-Smart Accelerator in Senegal. As the Accelerator-technical assistance is implemented, companies are likely to double climate change mitigation and adaptation impacts. Major interventions driving changes are: climate information services (CIS), water and soil management (Adaptation); agroforestry, efficient fertilizers use, and renewable energy (Mitigation); improved ag-practices and food loss reduction (Productivity). Although there have been significant improvements, there are several opportunities to further enhance impacts. This can be achieved following these principles: (1) avoid land-use change; (2) implement soil conservation practices; (3) enhance production diversity; (4) use of improved crop varieties and livestock breeding-feeding; (5) efficient use of water-energy-fertilizer; (7) avoid food-loss; (8) use of renewables; (9) CIS adoption, and (10) promote women-youth participation. This note provides a baseline for comparison and indicates opportunities for enhancing climate resilience and food security through Accelerator-supported companies in Senegal.